Stiffness and vibrational characteristics of SMS/DER331 composites with shape memory alloy long fibers - Ibrahim@Tamrin, Mohd Norihan (2008)
SMA-composites are an adaptive composite in which SMA elements are incorporated into fiber reinforced epoxy composites. Many researches have been done on investigating the properties of shape memory effect and superelastic influence in SMA composites. However, little information available on the effect of different fiber volume fraction with continuous flexinol long wire to mechanical strength and vibrational characteristics. This study is mainly focused on the integration of shape memory alloy (SMA) elements with epoxy composites based on different fiber volume fraction. The aim is to analyze and investigate static and dynamic mechanical properties of SMAJDER331 by measuring the first vibration mode of clamped cantilever beams, elastic strength and hysteresis behavior of SMAcomposites through monotonic tensile, cyclic and vibration analysis. This observation indicates that the Young's modulus increases (1667.083MPa) at 2.4% fiber volume fraction of flexinol wire of SMAJDER331 compared to matrix Young's modulus (904.495MPa). The increase of temperature up to 75°C and 90°C lead to the recovery of stress and strain and therefore closed hysteresis achieved. TIle temperature dependency of vibration property is affected largely due to the addition of SMA Flexinol long fibers. The vibrational characteristics of SMA composites can be improved by the addition of certain amount of flexinol wire. The addition of 2.4% fiber volume fraction offlexinol long fibers resulted in the highest natural frequency with the value of 171 Hz at the temperature of 70° C.